2013
DOI: 10.2166/wst.2013.452
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and toxicological evaluation of transformation products during advanced oxidation processes

Abstract: The entry of pharmaceuticals into the water cycle from sewage treatment plants is of growing concern because environmental effects are evident at trace levels. Ozonation, UV- and UV/H(2)O(2)-treatment were tested as an additional step in waste water treatment because they have been proven to be effective in eliminating aqueous organic contaminants. The pharmaceuticals carbamazepine, ciprofloxacin, diclofenac, metoprolol and sulfamethoxazole as well as the personal care products galaxolide and tonalide were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Similarly, degradation products following the oxidation of CBZ by ozonation, UV and UV/H 2 O 2 processes exhibited no genotoxic, cytotoxic or estrogenic effects [258]. CBZ metabolites including 10,11-dihydro-trans-10,11-dihydroxy-carbamazepine, acidone and acridine formed during CAS process [256] have also been reported to be non-toxic [258,259]. Although degradation products or metabolites of CBZ formed during CAS and AOPs are non-toxic, Bu et al [255] reported that CBZ-2,3-arene (one oxide intermediate) is believed to cause idiosyncratic effect after CBZ consumption for medicinal purposes [255].…”
Section: Fate and Metabolites Of Cbzmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, degradation products following the oxidation of CBZ by ozonation, UV and UV/H 2 O 2 processes exhibited no genotoxic, cytotoxic or estrogenic effects [258]. CBZ metabolites including 10,11-dihydro-trans-10,11-dihydroxy-carbamazepine, acidone and acridine formed during CAS process [256] have also been reported to be non-toxic [258,259]. Although degradation products or metabolites of CBZ formed during CAS and AOPs are non-toxic, Bu et al [255] reported that CBZ-2,3-arene (one oxide intermediate) is believed to cause idiosyncratic effect after CBZ consumption for medicinal purposes [255].…”
Section: Fate and Metabolites Of Cbzmentioning
confidence: 98%
“…In another study, Jelic et al [160] investigated the toxicity of the media in a pulsed fluidized bed bioreactor containing whole-cell T. versicolor and CBZ at an initial concentration of 500 µg/L. The acute toxicity test (Microtox) showed the toxicity induced by CBZ was reduced from 95% to 24% after an incubation time of 10 days, suggesting that the degradation products were non-toxic [258]. Similarly, degradation products following the oxidation of CBZ by ozonation, UV and UV/H 2 O 2 processes exhibited no genotoxic, cytotoxic or estrogenic effects [258].…”
Section: Fate and Metabolites Of Cbzmentioning
confidence: 99%
See 1 more Smart Citation
“…5, the CAR metabolites acridine and 3-hydroxy carbamazepine were found in the digestate samples, indicating effective transformation in the substrate or during biogas production (AD). Surprisingly, the CAR transformation product carbamazepine-10,11-epoxide, usually identied as the main CAR transformation product in waste water and other biologically active matrices, [70][71][72] was not detected in the digestate samples investigated here.…”
Section: Contaminants Of Emerging Concern In Liquid Digestatesmentioning
confidence: 63%
“…Janzen et al [50] found several stable transformation products during ozonation of polycyclic musk fragrances (no removal of musk xylene and musk ketone was obtained) and indicated that contact times of more than 15 min would be required to remove at least some of these transformation products. Accompanying analysis during an ozonation study by vom Eyser et al [51], focusing on galaxolide and tonalide next to five pharmaceuticals, showed no genotoxic, cytotoxic or oestrogenic potential for the investigated compounds after oxidative treatment (ozonation, UV and UV/H 2 O 2 treatment) of real wastewaters, indicating no hazardous impact of by-product formation from ozonation and other AOPs. Margot et al [3] reported no removal of galaxolidone, a fragrance metabolite, during the ozonation of a WWTP effluent.…”
Section: Synthetic Musk Fragrancesmentioning
confidence: 92%